EFEK EKSTRAK BAYAM MERAH VARIETAS MIRA TERHADAP GLUKOSA DARAH PUASA DAN MALONDIALDEHID TIKUS MODEL DMT2 - Nilasari, Aprilina Citra Ayu; Wiboworini, Budiyanti; Listyawati, Shanti (Media Penelitian dan Pengembangan Kesehatan, 2024)
Persistent hyperglycemia in type 2 diabetes mellitus (T2DM) increases the risk of lipid peroxidation that produces malondialdehyde (MDA). Red spinach mira extract (RSME) contains anthocyanins and beta carotene, both of which have the potential as antioxidants in reducing fasting blood glucose (FBG) and MDA levels. The purpose of the study was to determine the effect of RSME administration on FBG and MDA levels in T2DM. The research method was true-experimental with pretest-posttest. The study used 30 male Wistar rats, and divided into 5 groups, namely the normal group and given  standard diet, K- T2DM rats and given a standard diet, K+ T2DM rats and given acarbose drug therapy 1.8 mg/200g/day, P1 T2DM rats and given a dose of RSME 688 mg/200g Body weight (BW) and P2 T2DM rats and given a dose of RSME 1376 mg/200g BW for 14 days. Statistical analysis of FBG and MDA using One Way Anova test and continued with Post Hoc test to determine the difference between groups, while to determine the effect using Paired t-test. The results of the study after intervention for 14 days, all groups given RSME experienced a decrease in FBG levels P1 by 158.60 mg/dl (p=0.000), KP2 by 180 mg/dl (p=0.000) and MDA KP1 decreased by 6.01 nmol/mL (p=0.000) and KP2 by 7.75 nmol/mL (p=0.000) and there was significant value (p<0.05). The study concluded that the best dose is KP2, which reduces FBG levels by 180.84 mg/dl and MDA by 7.75 nmol/ml, the highest decrease compared to the other doses.